2015
DOI: 10.1097/sih.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Virtual Human Vignette to Compare Nurses’ Assessment and Intervention Choices for Pain in Critically Ill Children

Abstract: Introduction As virtual experiences are increasingly used in healthcare training and research, it is important that adequate processes are applied for developing valid scenarios. We describe the development and validation of virtual human (VH) vignettes, computer-generated scenarios with animated patients and clinical information, for a mixed-methods study regarding nurses’ assessment and intervention choices for critically-ill children’s pain. Methods We followed the Case Development and Review Process for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
(38 reference statements)
2
16
0
Order By: Relevance
“…Methods for this study have been reported in prior publications, and additional details regarding the instruments as well as data collection and analysis can also be obtained elsewhere (LaFond, Van Hulle Vincent, Corte, et al, 2015; LaFond, Van Hulle Vincent, Lee, et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods for this study have been reported in prior publications, and additional details regarding the instruments as well as data collection and analysis can also be obtained elsewhere (LaFond, Van Hulle Vincent, Corte, et al, 2015; LaFond, Van Hulle Vincent, Lee, et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Because the PBPQ was adapted for this study, content validity was assessed through expert review; four advanced practice nurses with an average of 10 years’ experience in pediatric critical care affirmed the accuracy and relevance of content for PICU nurses (LaFond, Van Hulle Vincent, Corte, et al, 2015; LaFond, Van Hulle Vincent, Lee, et al, 2015). Further, a PICU clinical pharmacist confirmed accuracy and relevance of opioid kinetics items.…”
Section: Methodsmentioning
confidence: 99%
“…Four advanced practice nurses with expertise in care of critically ill children reviewed the adapted PBPQ for accuracy of content and applicability to the PICU. Details regarding this process have been previously reported (LaFond et al, in press). …”
Section: Methodsmentioning
confidence: 99%
“…A description of the development and validation of the VH vignettes can be read elsewhere (LaFond et al, in press). Each VH vignette depicts a boy in the PICU; nurses visualize his current behavior, vital signs, and reported level of pain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation